The spatiotemporal domains of natural climate solutions research and strategies for implementation in the Pacific Northwest, USA - Chafe, Oriana E.; Broz, Adrian P.; Levenson, Eric S.; Farinacci, Michael D.; Anderson, Riley O.; Silva, Lucas C. R. (Frontiers in Climate, 2024)
Natural climate solutions have been proposed as a way to mitigate climate change by removing CO2 and other greenhouse gases from the atmosphere and increasing carbon storage in ecosystems. The adoption of such practices is required at large spatial and temporal scales, which means that local implementation across different land use and conservation sectors must be coordinated at landscape and regional levels. Here, we describe the spatiotemporal domains of research in the field of climate solutions and, as a first approximation, we use the Pacific Northwest (PNW) of the United States as a model system to evaluate the potential for coordinated implementations. By combining estimates of soil organic carbon stocks and CO2 fluxes with projected changes in climate, we show how land use may be prioritized to improve carbon drawdown and permanence across multiple sectors at local to regional scales. Our consideration of geographical context acknowledges some of the ecological and social challenges of climate change mitigation efforts for the implementation of scalable solutions.